Geography of placemories: deciphering spatialised memories. (January 2023) - Hubner, Elena; Dirksmeier, Peter
This paper develops the new concept of the geography of placemories as a critical approach for deciphering spatialised memories in cultural geography. In referring to Alfred North Whitehead's philosophy of organism and cultural materialism in line with Raymond Williams, the paper reflects on processual conceptions of feeling, society, memory and place. First, reviewing existing research on memory and place elucidates that cultural geography takes spatialised memories as fixed objects. Its analysis leads to statements about society. Second, to avoid this fallacy, the paper shifts the analytical basis for the cultural geographical conception of memorial sites from place to feelings and experiences by developing a new view on spatialised memory. The resulting processual problematisation of the ontology of memories, as well as its relevance for the present and spatialisations, is called the placemoric approach. The analysis of contested remembering processes with regard to the prerogative of interpretation of half-timbered houses in descriptions of Nuremberg's old town in North Bavaria, Germany demonstrates the capabilities of the placemoric approach. In doing so, the paper shows how spatialised memories are the socially constructed result of permanently changing feelings.